SOSIAL EKONOMI DAN KESEJAHTERAAN NELAYAN DI WILAYAH TELUK JAKARTA: LITERATURE REVIEW - Parenrengi, Sudarmin; Yunas, Satria; Hilmiyah, Nurul (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Abstract This research is a literature review with the aim of producing a study of the results of previous studies related to social, economic, environmental and welfare of fishermen, especially in the bay area of ​​Jakarta. The results of the research carried out by previous researchers focused a lot on environmental issues, reclamation and a little discussion on social, economic, environmental and welfare issues of fishermen. The results of the literature review show the phenomenon of problems surrounding fishermen and their lives in the Jakarta Bay area which includes social, economic, environmental and welfare aspects. The results of the study indicate that the study has not been carried out comprehensively, integrated and sustainable and has not shown any impact from the results of previous studies. Research on literature review with the title of Socio-Economic and Fishermen's Welfare in the Jakarta Bay Area is focused more deeply by using exploratory research methods on the sample results of previous studies using secondary data in the period 2003-2018. This research literature review is expected to be a reference to improve the research framework that is more integrative, synergistic and sustainable so that it can answer existing problems. Keywords: Literature review, economy, welfare, fishermen, explorative.